The Role of Teachers in Implementing the Independent Curriculum at Lokon St. Nicolaus Tomohon - Senduk, Meiny (International Journal of Information Technology and Education, 2024)
This research aims to explore the role of teachers in implementing the Independent Curriculum using a qualitative approach. The Merdeka Curriculum is a new initiative within the framework of Merdeka Belajar which aims to renew the education system in Indonesia. The main focus of the Merdeka Curriculum is to introduce a curriculum framework that is more flexible, oriented to the essence of the material, and develops students’ character and competencies. This research focuses on teachers’ experiences and practices in dealing with these curriculum changes. This research uses a qualitative approach with data collection techniques through interviews, observation, and document analysis. The research subjects were teachers at Lokon St. Middle School. Nikolaus Tomohon, who has implemented the Independent Curriculum. Data were analyzed using a descriptive approach to identify the teacher’s role in planning, implementing, and evaluating learning following the principles of the Independent Curriculum. Research findings show that teachers have a significant role in implementing the Independent Curriculum. They have adopted various learning strategies that are diverse, innovative, and creative in dealing with these curriculum changes. Apart from that, teachers also play an important role in facilitating student-centered learning, motivating students, and developing their character and competencies. This research contributes to the understanding of the role of teachers in the implementation of the Independent Curriculum and provides insight for the development of more effective education policies. The practical implication of this research is the importance of support and development of teacher professionalism in facing curriculum changes. This research also provides a basis for further research on the implementation of the Independent Curriculum in the Indonesian education context.